A Survey of Emergency Department 2009 Pandemic Influenza A (H1N1) Surge Preparedness—Atlanta, Georgia, July–October 2009 - Sugerman, David (Clin Infect Dis, 2011)
During August through September 2009, a surge in emergency department (ED) visits for 2009 pandemic influenza A (pH1N1) illness occurred in Georgia, particularly among children. To understand surge preparedness and capacity, we obtained influenza-like illness (ILI) ED visit data from the Georgia State Electronic Notifiable Disease Surveillance System (SendSS) and conducted a retrospective, Internet-based survey among all 26 metro Atlanta ED managers with reference to the period 1 July–1 October 2009. SendSS detected a marked and progressive increase in mean monthly ILI visits from 1 July–1 October 2009, which more than tripled (from 399 to 2196) for the 2 participating EDs that cared for pediatric patients during this time. ED managers reported patient volume surges, resulting in space and supply limitations, especially at pediatric EDs. Most (92%) of the facilities had current pandemic influenza plans. Pandemic planning can help to ensure preparedness for natural and man-made disasters and for future influenza pandemics.